2018
DOI: 10.5582/ddt.2018.01033
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in the elderly in a Japanese long-term medical facility: An ultrasonographic investigation

Abstract: This study aims to assess the fecal retention in elderly patients using colonic ultrasonography (US) in Japanese long-term care facility and determine the correlation between nutrition management methods and the fecal retention by US. This cross-sectional, single-center study was conducted in a long-term care facility in Japan. Patients with chronic constipation fulfilled the Rome III criteria for the diagnosis of functional constipation. US was performed on constipation patients with 4-day fecal retention bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Therefore, it is unlikely that the knowledge on defecation care or this algorithm affected the intervention. In our previous study at a long‐term care facility, although 56.3% of the patients assessed for constipation actually had loose stools, all patients received suppository doses as routine care . Furthermore, individualized intervention reportedly improves symptoms related to constipation .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, it is unlikely that the knowledge on defecation care or this algorithm affected the intervention. In our previous study at a long‐term care facility, although 56.3% of the patients assessed for constipation actually had loose stools, all patients received suppository doses as routine care . Furthermore, individualized intervention reportedly improves symptoms related to constipation .…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study at a long-term care facility, although 56.3% of the patients assessed for constipation actually had loose stools, all patients received suppository doses as routine care. 15 Furthermore, individualized intervention reportedly improves symptoms related to constipation. 22 Further studies at long-term care facilities or hospitals where routine care is carried out to treat constipation are required to show the efficacy of individualized defecation care based on US assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that stool retention can be confirmed by observing the hyperechoic region of the rectum. Furthermore, it has been reported that a hyperechoic region is also found in the rectum of patients with functional constipation (30)(31)(32). The strong hyperechoic region with acoustic shadow in the rectum indicates the presence of hard stool and has been suggested to be able to identify IBS.…”
Section: Drug Discoveries and Therapeutics Advance Publication P3mentioning
confidence: 99%
“…Therefore, we will consider whether objective indicators can be used to predict and prevent faecal incontinence in unconscious patients in advance. In recent years, it has been reported that faecal retention can be objectively and noninvasively evaluated using ultrasound imaging equipment [42][43][44][45]. In addition, another previous study using ultrasound reported that gallbladder contraction was higher in the IBS group than in the control group, both in the fasted state and after dietary stress [46,47].…”
Section: Can Faecal Incontinence In Unconscious Patients Be Predicted and Prevented In Advance?mentioning
confidence: 99%